Relevance of the Materno-Fetal Interface for the Induction of Antigen-Specific Immune Tolerance - Mimoun, Angelina; Delignat, Sandrine; Peyron, Ivan; Daventure, Victoria; Lecerf, Maxime; Dimitrov, Jordan D.; Kaveri, Srinivas V.; Bayry, Jagadeesh; Lacroix-Desmazes, Sébastien (Frontiers in Immunology, 2020)
In the human, maternal IgG are transferred to the fetus from the second trimester of pregnancy onwards. The transplacental delivery of maternal IgG is mediated by its binding to the neonatal Fc receptor (FcRn) after endocytosis by the syncytiotrophoblast. IgG present in the maternal milk are also transferred to the newborn through the digestive epithelium upon binding to the FcRn. Importantly, the binding of IgG to the FcRn is also responsible for the recycling of circulating IgG that confers them with a long half-life. Maternally delivered IgG provides passive immunity to the newborn, for instance by conferring protective anti-flu or anti-pertussis toxin IgG. It may however lead to the development of autoimmune manifestations when pathological autoantibodies from the mother cross the placenta and reach the circulation of the fetus. In the recent years, strategies that exploit the transplacental delivery of antigen/IgG complexes or of Fc-fused proteins have been validated in mouse models of human diseases to impose antigen-specific tolerance, particularly in the case of Fc-fused factor VIII (FVIII) domains in hemophilia A mice or pre-pro-insulin (PPI) in the case of type 1 diabetes (T1D). The present review summarizes the mechanisms underlying the FcRn-mediated transcytosis of IgG, the physiopathological relevance of this phenomenon and the repercussion for drug delivery and shaping of the immune system during its ontogeny.